We have, f: R → R and g: R → R are two functions defined by
f (x)= x2 and g(x) = x + 1
fog (x) = f(g(x)) = f(x + 1) =(x + 1)2
⇒ fog(x) = x2 + 2x + 1 ……(i)
gof(x) = g(f(x)) = g(x2) = x2 + 1 ……(ii)
from (i) & (ii)
fog ≠ gof
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation